Correlation between pregnancy-induced hypertension and ocular disorders - Halim, Tanzila; Islam, M. Saiful; Khatun, Hasina; Khan, Amena; Hasan, M. Mehedi; Kulsum, Umme (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Pregnancy-induced hypertension (PIH) is a common condition that can lead to significant maternal and fetal complications. Ocular manifestations, including hypertensive retinopathy, are frequently observed in PIH and may reflect the severity of the disease. This study aimed to evaluate the correlation between PIH and ocular disorders, as well as the associated maternal and fetal outcomes. Methods: This retrospective observational study was conducted in the department of obstetrics and gynaecology at Mymensingh Medical College Hospital, Mymensingh and BSMMU, Dhaka, Bangladesh, from June 2018 to May 2020. A total of 120 pregnant women diagnosed with pregnancy-induced hypertension (PIH) were included based on specific inclusion criteria, which required a clinical diagnosis of PIH, gestational hypertension, preeclampsia, or eclampsia. Data were collected from medical records, including demographic details, clinical findings and ophthalmic evaluations. Results: Among the participants, 25% had hypertensive retinopathy, 12.5% exhibited visual field defects and 20.8% had no ocular complications. Severe PIH was significantly associated with ocular disorders (p=0.001). Maternal complications occurred in 37.5% of those with ocular changes, while 25% experienced preterm delivery and 20.8% had fetal growth restriction. All associations were statistically significant (p<0.05), highlighting the impact of ocular complications on maternal and fetal outcomes. Conclusions: The study demonstrated a strong correlation between the severity of PIH and ocular disorders, with hypertensive retinopathy being the most prevalent. Ocular complications were linked to adverse maternal and fetal outcomes, highlighting the importance of early ocular screening in PIH patients.